Waqf As A Device Means To Improve The Health Care And Sustenance Of The Refugee Camps Of North Eastern Nigeria - Muhammad Auwal Sulaiman; Ibrahim Abubakar Muhammad (al-Afkar, Journal For Islamic Studies, 2023)
The North-Eastern region of Nigeria has the highest concentration of border communities, and these contributed to the border-related misconducts, such as the activities of Boko Haram which forced many communities to relocate to safety areas for their comfort of life. Consequently, this situations finally placed many individuals and communities into Internally Displaced Persons (IDPs). This paper investigated the serious challenges faced by these IDPs in relation to shortage of access to health care facilities. The paper revealed how these IDPs were deprived to carry their economics activities such as farming, fishing and access to education as a result of the conflict in the lake Chad region, as well as the cross-border activities from extremist group. Using descriptive and analytical method, this paper states the position of Islam on Waqf as device means of relief on the communities facing the hardship situations. (Waqf is a voluntary charity in terms of land and property and is proven to be a strong instrument to reduce various burdens of life). The paper called on the attention of individuals, Non-Governmental organizations and Muslims countries to establish a permanent institution that will address these challenges and provide emergency services to this communities. Meanwhile, the paper recommends how this will be designed in order to reach the targeted communities.